Bioethanol production from waste hamburger by enzymatic hydrolysis and fermentation. (10th August 2020) - Han, Wei; Liu, Yanxu; Xu, Xiaobin; Huang, Jingang; He, Hong; Chen, Long; Qiu, Shanshan; Tang, Junhong; Hou, Pingzhi
Abstract: Hamburger is one of the largest parts of fast food in the world. The feasibility of bioethanol production from waste hamburger (WH) by enzymatic hydrolysis (commercial α-amylase) and fermentation was investigated in this study. Different enzyme loading volumes (B1: 0.02 mL/L, B2: 0.08 mL/L and B3: 0.14 mL/L) were used to evaluate the hydrolysis efficiency. The maximum chemical oxygen demand of 74.2 g/L, reducing sugar (RS) of 39.2 g/L and hydrolysis efficiency of 0.784 g RS/g WH could be achieved with B3. The reduction rate of WH could reach 76.8%–80.4%. The ethanol fermentation could be finished within 50 h since the soluble nutrient pretreated by α-amylase was easy to be used by the yeast. The highest ethanol production of 27.4 g/L and ethanol yield of 0.271 g ethanol/g WH (0.34 g ethanol/g TS) were achieved with B3. The waste hamburger hydrolysate is a promising substrate for bioethanol production and has high potential for industrial application. Highlights: Enzymatic hydrolysis of waste hamburger could be used for bioethanol production. Enzyme loading volumes determine the hydrolysis efficiency. Enzymatic hydrolysis has a good reduce efficiency for organic waste treatment. Nutrient lose happens with higher nutrient contents when sterilization was not applied. The highest ethanol yield of 0.271 g ethanol/g WH (0.34 g ethanol/g TS) were achieved.